Application of Disordered Organic Semiconductor Theory to Low Temperature Curing of Epoxy Resins - Aitken, Edward A. (Journal of Research Updates in Polymer Science, 2014)
The steep autocatalytic feature in a highly accurate DSC study of the heat rate from curing an epoxy resin with piperidine at 27.5 Deg C could not be explained using chemical kinetic power laws usually applied to curing epoxy resin products at higher temperatures. The theory of disordered conjugated organic semiconductors developed in the last decade has been applied to the observed heat rate data. Four heat rate sources have been identified to completely account for the experimental data. Two of the four sources generating 80% of the heat are consistent with mobility change of ion pairs indicating that the low temperature cure follows an organic semiconductor mechanism. It was shown that autocatalysis did not begin until about one fiftieth of the epoxy rings were opened (ignition). After ignition the heat rates of two propagation mechanisms grow exponentially. One charge transport mechanism generates a small heat rate but grows immediately after ignition due to an increase in ion pairs by the dopant (piperidine). The second mechanism appears later but becomes dominant, peaking at 50% completion, where the heat rate is about 50 times higher than the start of the first mechanism. The rate increase is attributed to localized energy sites that lower the LUMO level closer to the HOMO level of the monomer increasing the mobility (heat rate).